Developing Intercultural Competence Awareness in Language Classroom: A View from FL Teachers - Muh. Arif; Harni Jusuf (Al-Lisan: Jurnal Bahasa, 2022)
Language and culture are now considered interwoven, as culture becomes an integral part of learning a foreign language. This study aims to ascertain FL lecturers' perspectives on intercultural education and classroom procedures, including instructional materials, classroom activities, assessment, and the role of teachers in fostering intercultural awareness. Six lecturers were surveyed in this study. The six lecturers include three Arabic language education lecturers and three English language education lecturers with roughly five years of teaching experience. The data collection instrument is an interview guideline. The findings indicated that instructors acknowledged the importance of integrating culture into FL classrooms via various strategies and methods. Their statements include the following: they are frequently compelled to keep to textbook activities and activities previously prepared for the textbook since they have little time in class to address cultural concerns due to the syllabi's high expectations.